TAFIẒ LEARNING MANAGEMENT IN IMPROVING STUDENTS 'INTERESTS IN MEMORING THE ALQURAN IN YAYASAN TAHFIDZUL QURAN AL-FAWWAZ MEDAN - Candra Wijaya; M Fajri Syahroni Siregar; Muhammad Ruslan; Syahrul Holid; Roslaeni Roslaeni (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This study aims to determine the management of learning Taḥfiẓ Alquran which includes planning and organizing learning, implementing the learning and evaluating learning. This research is qualitative with a case study model. The collection method uses observation, interviews and also does documentation. The results showed that: (1) Management of learning Taḥfiẓ Alquran in increasing interest in memorizing the Koran at the Taḥfiẓ Al-Fawwaz Foundation includes: (a) learning planning consisting of memorization targets, learning objectives, learning programs, time allocation to learning tools, (b) learning that has a teaching team organization division and students are also grouped, (c) the implementation of learning which consists of learning activities and learning motivation, (d) learning evaluation.